Lower Ventromedial Prefrontal Cortex Glutamate Levels in Patients With Obsessive–Compulsive Disorder - Batistuzzo, Marcelo C.; Sottili, Bruna A.; Shavitt, Roseli G.; Lopes, Antonio C.; Cappi, Carolina; de Mathis, Maria Alice; Pastorello, Bruno; Diniz, Juliana B.; Silva, Renata M. F.; Miguel, Euripedes C.; Hoexter, Marcelo Q.; Otaduy, Maria C. (Frontiers in Psychiatry, 2021)
Background: Recent studies using magnetic resonance spectroscopy (¹H-MRS) indicate that patients with obsessive-compulsive disorder (OCD) present abnormal levels of glutamate (Glu) and GABA in the frontal and striatal regions of the brain. These abnormalities could be related to the hyperactivation observed in cortico-striatal circuits of patients with OCD. However, most of the ¹H-MRS previous studies were not capable of differentiating the signal from metabolites that overlap in the spectrum, such as Glu and glutamine (Gln), and referred to the detected signal as the composite measure - Glx (sum of Glu and Gln). In this study we used a two-dimensional JPRESS ¹H-MRS sequence that allows the discrimination of overlapping metabolites by observing the differences in J-coupling, leading to a higher accuracy in the quantification of all metabolites. Our objective was to identify possible alterations in the neurometabolism of OCD, focusing on Glu and GABA, which are key neurotransmitters in the brain that could provide insights about the underlying neurochemistry of a putative excitatory/inhibitory imbalance. Secondary analysis including metabolites such as Gln, creatine (Cr), N-acetylaspartate, glutathione, choline, lactate, and myo-inositol were performed. Methods: Sixty patients with OCD and forty-two healthy controls (HC) underwent 3T ¹H-MRS in the ventromedial prefrontal cortex (vmPFC, 30x25x25mm³). Metabolites were quantified using ProFit (version 2.0) and Cr as a reference. Furthermore, Glu/GABA and Glu/Gln ratios were calculated. Generalized linear models (GLM) were conducted using each metabolite as a dependent variable and age, sex, and gray matter fraction (fGM) as confounding factors. GLM analysis was also used to test for associations between clinical symptoms and neurometabolites. Results: The GLM analysis indicated lower levels of Glu in patients with OCD (z = 2.561; p-value = 0.010). No other comparisons reached significant differences between groups for all the metabolites studied. No associations between metabolites and clinical symptoms were detected. Conclusions: The decreased Glu concentrations in the vmPFC of patients with OCD indicate a neurochemical imbalance in the excitatory neurotransmission that could be associated with the neurobiology of the disease and may be relevant for the pathophysiology of OCD.